Menurunkan Waktu Penggantian Tabung Gas Welding (GMAW) Menggunakan Metode Single Minute Exchange Die (SMED) di Politeknik Astra - Neilinda Novita Aisa; Rahayu Budi Prahara; Eduardus Dimas Arya Sadewa; Wahyudi Wahyudi; Andreadie Wicaksono (Universitas Teuku Umar, 2023)
Politeknik Astra is a high vocational education institution that have several laboratories. Welding laboratoy has longest preparation time compare to another laboratories. Gas cylinder changes process in Gas Metal Arc Welding (GMAW) takes 29.2 minutes, which is the longest preparation time so the welding training is hinder by it. Previous condition of gas instalation is, every GMAW machine equiped with one gas cylinder, so if the cylinder is run out of gas, it have to changes and potentially it could be done more than one machine. The aim of this research is to reduce gas cylinder changes time in welding laboratory using single minute exchange of dies methode (SMED). SMED is one of lean manufacturing metodes that able to identified and reduce or eliminate time waste by separated internal setup and external setup. Using SMED metods, gas cylinder changes activities are identified then divided by internal and external setup. The activities that have no effect to gas flow from cylinder to machine are convert from internal to external setup. For the final, external setup are simplified using 5W2H tools. The solution that reserearcher found using SMED method is to built a centralized gas system with one cylinder as an active gas supply for whole GMAW machine and the other one as a backup cylinder, in stead of install gas cylinder on every GMAW machine. The result of this research is setup time for gas cylinder changing process is reduce from 1752 seconds or 29.2 minutes to 877 seconds or 14.6 minute or reduce 50%, furthermore man power alaso reduce from 3 person to 1 person.